PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SDS BINA TARUNA 3 MEDAN - Saragih, Widhyani; Julia, Nur Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low critical thinking ability of grade III students at SDS Bina Taruna 3 Medan in mathematics, with a sample of 30 students. The purpose is to determine the effect of problem-based learning on students' mathematical critical thinking regarding data presentation in tables. The method uses a quantitative approach with a one-group pretest-posttest design in one class, conducted in two stages before and after treatment. Results indicate the instrument met validity and reliability tests. The normality test showed a non-normal distribution, so the Wilcoxon Signed Ranks Test was applied. Analysis reveals Sig. 0,000 < 0,05, meaning H₀ is rejected and H₁ is accepted. The N-gain score is 0.63, categorized as medium. The conclusion proves that problem-based learning influences students mathematical critical thinking ability.